Antara Ragu dan Tak Cocok: Faktor-Faktor yang Mendorong Penghindaran Konsumen - Haryanti, Novi; Atmaja, Ferry Tema (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The purpose of this study is to examine the relationship between product suitability uncertainty, product quality uncertainty, and perceived risk in influencing consumer avoidance of new cosmetic products on e-commerce platforms. The method used is a quantitative approach with data collection through an online questionnaire using the T-Survey platform. The research sample consisted of 220 respondents who met the criteria of having purchased or intending to purchase new cosmetic products through e-commerce. Data was analyzed using the SEM method in the SmartPLS application. The results indicate that uncertainty regarding product suitability and uncertainty regarding product quality have a positive and significant influence on perceived risk and consumer avoidance. However, the influence of perceived risk on consumer avoidance was found to be insignificant. This finding indicates that in the context of online purchases, uncertainty about product information is more likely to drive consumers to avoid products than the perception of risk itself.